Pemanfaatan Pasir Lokal Kecamatan Palaran Kota Samarinda Kalimantan Timur sebagai Material Pembuatan Beton Normal - Achmad, S.T., M.T, Karmila (Jurnal Teknologi Terpadu, 2025)
The local sand utilization is expected as an alternative to achieve more efficient construction cost. The availability of adequate local sand in Samarinda is located in Palaran sub-district. Palaran sub-district is the third largest sub-district of 10 sub-districts in Samarinda. Geographically, the sub-district has 5 villages with a land area of 156.29 km2. Besides Palu sand, the local community generally uses two local sand types for construction, mountain sand in Bantuas village and river sand in Handil Bakti village. This study aims to obtain an alternative local sand material for forming concrete having good concrete compressive strength. For this reason, some sand material tests will be carried out: gradation tests, specific gravity and absorption, water content, mud content and unit weight. For the gravel test, the sand test is added with an abrasion test. The concrete compressive strength test result showed local sand from the mountain sand of Bantuas village has a higher compressive strength compared to other variations, concrete using Palu sand and concrete using Handil Bakti Village River sand. The results of the 14-day compression test obtained the concrete strength using mountain sand from Bantuas Village of K-304.60, river sand from Handil Bakti Village of K-240.27, and Palu sand of K-248.27. While,the 28-day compression test result obtained the concrete strength using mountain sand from Bantuas Village of K-337.68, river sand from Handil Bakti Village of K-247.06, and Palu sand of K-274.40.